Adipokine ZAG Alters Depression-Like Behavior by Regulating Oxidative Stress in Hippocampus - Sun, Huangbing; Ma, Fuli; Chen, Wenjing; Yang, Xiaojing (Hormone and Metabolic Research, 2022)
Zinc-α2-glycoprotein (ZAG) is an adipokine involved in body metabolism, and now it has been shown to be present in the brain and play a role in some neurological diseases such as epilepsy and Alzheimer’s disease. In the present study, we employed ZAG knockout (KO) mice to investigate the effects of ZAG on behaviors after fasting and in vitro used overexpression (OV) ZAG in HT-22 cells to further clarify the possibly underlying mechanism. The results showed that ZAG exists widely in the brain tissues of mice and significantly increased during fasting. In ZAG KO group the depression-like behaviors were significantly increased after fasting for 24 hours, meanwhile the hippocampal reactive oxygen species (ROS) content was significantly increased. In vitro, serum deprivation led to the increasing of neuronal death and ROS, the reduced mitochondrial membrane potential and ATP levels, while ZAG overexpression alleviated these negative effects. The β3 adrenoreceptor (β3AR)/protein kinase A (PKA)/cAMP response element-binding (CREB) pathway possibly mediated the effects of ZAG on antioxidation. These results proposed a possible target for novel therapeutic approaches to the treatment of depression and provide potential link between adipose tissue and psychiatric disease.
Keywords: zinc-α2-glycoprotein; oxidative stress; depression; hippocampus